Analysing the problem-solving ability through the Problem-Based Learning model on the subject statistics in the grade VIIIB of Kanisius junior high school Kalasan - Pandu, Y K; Prabaningrum, C P (Journal of physics. Conference series, 2020)
Through the conduct of the study, the researcher would like to: (1) describe the learning stages for the subject Statistics through the implementation of the problem-based learning model; and (2) identify the problem-solving skills of the Grade VIIIB students in the Kanisius Junior High School Kalasan for the subject Statistics. As a result, the study belonged to the design research. During the conduct of the study, the subjects who have been involved were the students of Grade VIIIB Kanisius Junior High School Kalasan and the study itself took place from March until April 2019. Then, the data gathering method that had been implemented was the documentation record and the learning test administration while the instrument that had been implemented was the field note and learning test results. After the data had been gathered, the subsequent stage was data reduction, data presentation and conclusion drawing or verification. In overall, the results of the study show that: (1) the learning stages in the problem-based learning model for the subject Statistics with two meetings have already been in accordance to the design; and (2) the problem-solving skills among the students have been various. In the first subject, four out of five indicators of mathematical problem-solving skills by NCTM have been met. On the contrary, in the second subject the five indicators of mathematical problem-solving skills according to NCTM have been met.